Controlling porosity and ultraviolet photoresponse of crystallographically oriented ZnO nanostructures grown by pulsed laser deposition. (15th March 2019) - Soni, Ankit; Mavani, K.R.
Abstract: We have synthesized a series of porous nanostructures of c -axis oriented wurtzite ZnO using glancing angle pulsed laser deposition. During deposition, the oxygen partial pressure (PO2 ) was varied to study the effects on growth, porosity and optical properties. With varied PO2 the growth of nanostructure changes gradually without losing its crystallographic orientation. The variation in PO2 causes systematic change in porosity of these nanostructures, which strongly influences ultraviolet photoresponse. These results show that the parameters such as surface morphology, growth and porosity as well as the optoelectronic properties can be controlled by variation in PO2 without compromising the crystalline structure. Graphical abstract: Unlabelled Image